2023
DOI: 10.3390/ijerph20031798
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hospital Readiness to Respond to COVID-19 Pandemic in Jordan—A Cross Sectional Study

Abstract: During the global COVID-19 pandemic, hospitals faced tremendous pressure to cope with the emergency preparedness situations needed to cater for the influx of patients while maintaining their essential services. This study aimed to assess the level of readiness of hospitals in Jordan to respond to the COVID-19 pandemic using the WHO hospital readiness checklist. A cross-sectional survey using the modified and validated checklist was conducted in Jordan between 15 May and 15 June 2021. The checklist entailed ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…From the results of the profit web picture on the Hospital Readiness Checklist where the components of Occupational Health, Mental Health, and Psychosocial Support are the lowest the solution is through the Occupational Health and Safety (K3) Program in hospitals as a priority action. Related to this is supported by previous research in Jordan where the results of research there stated the component of psychological support and occupational health support is still low (Dahmash et al, 2023). Selain itu juga di perkuat beberapa penelitian tentang manajemen kesehatan dan keselamatan kerja di rumah sakit (Dewi & Wardani, 2022), (Efendy et al, 2022), (Bando et al, 2020),(Gómez Miranda & Gómez Miranda, 2018.…”
Section: Overview Of Hospital Readiness: Key Componentssupporting
confidence: 52%
See 1 more Smart Citation
“…From the results of the profit web picture on the Hospital Readiness Checklist where the components of Occupational Health, Mental Health, and Psychosocial Support are the lowest the solution is through the Occupational Health and Safety (K3) Program in hospitals as a priority action. Related to this is supported by previous research in Jordan where the results of research there stated the component of psychological support and occupational health support is still low (Dahmash et al, 2023). Selain itu juga di perkuat beberapa penelitian tentang manajemen kesehatan dan keselamatan kerja di rumah sakit (Dewi & Wardani, 2022), (Efendy et al, 2022), (Bando et al, 2020),(Gómez Miranda & Gómez Miranda, 2018.…”
Section: Overview Of Hospital Readiness: Key Componentssupporting
confidence: 52%
“…The government as a regulator regularly needs to monitor and evaluate hospital readiness in facing the COVID-19 pandemic as part of efforts to improve the quality of hospital services (Direktur Jenderal Pelayanan Kesehatan Kementerian Kesehatan RI, 2020a). In addition, healthcare experts globally have stressed the importance of strengthening health systems, particularly hospitals, for effective pandemic response to protect patients' rights to health and staff (Dahmash et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, after evaluating and comparing the results, it can be concluded that the proposed method in this study has good reliability and the prioritization of hospitals is reasonable. (20,22,24) Communication flows in a hospital with its partners during a catastrophic event, which indicate how reliable and effective this information is. Emergency medical information system (C3) (8,19) The number of vehicles available to the hospital Number of vehicles (T1) Transportation (9,20) Availability of helipad space for receiving patients transported by helicopter Helipad space (T2) (8,9,19) Access and routes to the hospital Location access (T3) (8,23,25) The number of hospital personnel Number of personnel (P1) Personnel (7,20,24,25) Indicating the level of disaster preparedness regarding employees and their behavior and coordination with each other in the event of an accident Manpower preparedness (P2) (7,8,25) Education level and work experience certificates for hospital staff in terms of disaster preparedness and their behavior and reaction at the time of accident.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…(20,22,24) Communication flows in a hospital with its partners during a catastrophic event, which indicate how reliable and effective this information is. Emergency medical information system (C3) (8,19) The number of vehicles available to the hospital Number of vehicles (T1) Transportation (9,20) Availability of helipad space for receiving patients transported by helicopter Helipad space (T2) (8,9,19) Access and routes to the hospital Location access (T3) (8,23,25) The number of hospital personnel Number of personnel (P1) Personnel (7,20,24,25) Indicating the level of disaster preparedness regarding employees and their behavior and coordination with each other in the event of an accident Manpower preparedness (P2) (7,8,25) Education level and work experience certificates for hospital staff in terms of disaster preparedness and their behavior and reaction at the time of accident. -0.017 -0.003 -0.008 0.028 0.006 0.003 -0.012 -0.012 0.001 -0.012 -0.012 0.003 -0.008 0.005 -0.005 0.015 0.002 -0.017 -0.062 7 H2 0.012 -0.028 -0.004 -0.030 0.006 0.003 -0.014 -0.012 0.001 -0.012 -0.012 0.003 0.044 0.032 -0.007 0.015 0.002 0.012 -0.063 8 H3 0.012 0.023 0.001 0.028 0.036 0.032 0.034 0.041 0.001 0.041 0.040 0.003 0.044 0.005 0.057 0.015 0.002 0.012 -0.005 5 H4 -0.017 -0.003 0.001 0.028 -0.025 -0.026 0.006 0.041 0.001 -0.012 -0.012 0.003 -0.008 -0.022 -0.004 0.015 -0.028 -0.017 0.442 1 H5 0.012 0.023 0.015 -0.030 0.006 0.032 0.020 -0.012 0.001 -0.012 -0.012 0.003 -0.008 0.005 -0.004 0.015 0.032 0.012 -0.066 9 H6 0.041 0.023 0.005 0.028 0.036 0.032 0.020 -0.012 0.001 -0.012 0.040 0.041 -0.008 -0.022 -0.001 0.015 0.032 0.041 0.079 4 H7 0.041 0.023 0.033 0.028 0.006 0.003 -0.006 -0.012 -0.029 -0.012 -0.012 -0.015 -0.008 0.005 -0.002 0.015 0.002 0.041 0.285 2 H8 -0.017 -0.028 -0.013 -0.030 -0.025 0.003 -0.017 -0.012 0.001 0.041 -0.012 -0.015 -0.008 0.005 -0.007 -0.043 0.002 -0.017 0.087 3 H9 -0.017 -0.003 -0.018 -0.030 0.006 -0.026 -0.020 0.041 0.031 -0.012 0.040 -0.015 -0.008 0.032 -0.007 -0.043 0.002 -0.017 -0.179 10 H10 -0.017 -0.003 -0.008 0.028 0.006 0.003 -0.012 -0.012 0.001 -0.012 -0.012 0.003 -0.008 0.005 -0.005 0.015 0.002 -0.017 -0.050 6 indexes ranked first to third, respectively.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…This lockdown was then extended to six weeks, during which only healthcare and essential sector providers were allowed to use vehicles. The public hospitals in Jordan faced immense pressure to handle the emergencies caused by the increase in COVID-19 patients while also continuing to provide critical services [23]. To address this issue, the Jordanian government set up six state hospitals, seventeen private hospitals, and six field hospitals across the country to provide treatment to those affected.…”
Section: Introductionmentioning
confidence: 99%